Scale-sensitive governance of the environment - Padt, Frans, 1961-; Opdam, Paul; Polman, Nico, 1969-; Termeer, Catrien (Wiley Blackwell, 2014)
Sensitivity to scales is one of the key challenges in environmental governance. Climate change, food production, energy supply, and natural resource management are examples of environmental challenges that stretch across scales and require action at multiple levels. Governance systems are typically ill-equipped for this task due to organisational and jurisdictional specialisation and short-term planning horizons. Further to this, scientific knowledge is fragmented along disciplinary lines and research traditions in academia and research institutions. State-of-the-art, Scale-Sensitive Govern.